Event-triggered Dynamic Output Feedback Controller for Discrete-time LPV Systems with Constraints⁎This work has been supported in part by the Brazilian Agencies CAPES under the project Print CAPES-UFSC "Automation 4.0" and CNPq; and by ANR project HANDY 18-CE40-0010. Issue 9 (2021) - de Souza, C.; Tarbouriech, S.; Castelan, E.B.; Leite, V.J.S.
Abstract: This paper examines an event-triggered control design approach for discrete-time linear parameter-varying (LPV) systems under control constraints. A parameter-dependent dynamic output-feedback controller with an event-triggering condition is designed to ensure the regional asymptotic stability of the closed-loop system while minimizing a quadratic cost function. Sufficient conditions are derived in terms of linear matrix inequalities (LMIs) thanks to the use of a parameter-dependent quadratic Lyapunov function. Also, convex optimization schemes are proposed using these conditions to minimize an upper bound of a given cost function or to maximize the size of the region of closed-loop stability. Examples illustrate the proposal.